2020
DOI: 10.1021/acs.iecr.0c03390
|View full text |Cite
|
Sign up to set email alerts
|

Facile Strategy to Construct High-Performance Nanofiltration Membranes by Synergy of Graphene Oxide and Polyvinyl Alcohol

Abstract: Graphene oxide (GO), as an emerging nanofiller, is commonly incorporated into the polypiperazine amide (PPA) selective layer to enhance nanofiltration (NF) performance. However, GO’s dispersibility and compatibility present outstanding challenges for fabricating high-performance GO-incorporated NF membranes. In this study, polyvinyl alcohol (PVA) and GO were introduced into the aqueous solution at the same time to enhance the membrane performance by taking advantage of the synergetic effects of GO and PVA. GO’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…(e) Trade-off relationship between water/salt selectivity (A/B) and water permeance (A). (f) Summary of water permeance and Na 2 SO 4 rejection of TFC NF membranes reported in previous literature. ,,, Error bars indicate the standard deviation ( n = 6).…”
Section: Results and Discussionmentioning
confidence: 99%
“…(e) Trade-off relationship between water/salt selectivity (A/B) and water permeance (A). (f) Summary of water permeance and Na 2 SO 4 rejection of TFC NF membranes reported in previous literature. ,,, Error bars indicate the standard deviation ( n = 6).…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is reported that the introduction of polyvinyl alcohol (PVA) in the aqueous phase during IP reaction, enhanced the dispersion and compatibility of GO resulting in fabrication of highly hydrophilic and defect-free membranes with improved antifouling performance and water permeance. 141 Similarly, synergetic impact of other additives along with 2D nanosheets could be explored. It has been observed that GO nanosheets have a greater impact on antibacterial properties than transport properties, while MoS 2 nanosheets provide enhanced permeation and salt rejection.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In PVA‐based TFC membrane PVA‐coating can be as a sole selective layer, as intermediate layer or both. Comprehensive studies on the modification of PIPA‐based NF membranes, using PVA, usually includes three strategies: inclusion of PVA into PIPA through IP route for formation of PIPA‐PVA layer, 133,134 formation of PVA‐based polymer layer as an intermediate layer (between the substrate and the top PIPA layer), 135,136 and coating PVA as a top selective layer 137 . Construction of interlayer is done to improve the IP reaction kinetics during the TFC membrane preparation, as well as to enhance the membrane performance.…”
Section: Pva‐based Membranes For Water Treatmentmentioning
confidence: 99%
“…PIPA/PVA/PES NF membrane, having PVA as intermediate layer, promoted the formation of nanoscale turning‐like structure, which improved the membrane permeability. While, use of GO nanomaterials along with PVA in the top layer resulted in a higher water permeation, 137 compared to PIPA‐PVA based composite membranes 133,134 . Wagh et al 138 modified polybenzimidazole (PBI)‐based NF membrane by incorporation of aquaporin into the selective layer.…”
Section: Pva‐based Membranes For Water Treatmentmentioning
confidence: 99%